Uniqueness of series with respect to general Franklin systems - G. Gevorkyan; A. Kamont (Հայաստանի ԳԱԱ)
We give some sufficient condition for the uniqueness of series with respect to general Franklin systems and discuss analogous results for orthonormal spline systems of higher order and some wavelet systems.
Keywords: Science; Mathematics